Measurement of the B0s → ϕϕ branching fraction and search for the decay B0 → ϕϕ - Aaij, Roel; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; et al. (Journal of high energy physics, 2015)
Using a dataset corresponding to an integrated luminosity of 3.0 fb−1 collected in pp collisions at centre-of-mass energies of 7 and 8 TeV, the Bs0 → ϕϕ branching fraction is measured to beℬBs0→ϕϕ=1.84±0.05stat±0.07syst±0.11fs/fd±0.12norm×10−5, where fs/fdrepresents the ratio of the Bs0to B0 production cross-sections, and the B0 → ϕK*(892)0 decay mode is used for normalization. This is the most precise measurement of this branching fraction to date, representing a factor five reduction in the statistical uncertainty compared with the previous best measurement. A search for the decay B0 → ϕϕ is also made. No signal is observed, and an upper limit on the branching fraction is set asℬB0→ϕϕ<2.8×10−8 at 90% confidence level. This is a factor of seven improvement compared to the previous best limit.
The LHCb Collaboration: R. Aaij, B. Adeva; M. Adinolfi, O. Aquines Gutierrez, P. d'Argent, S. Bachmann, A. Bien, J. Blouw, M. Britsch, S. Braun, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kecke, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, J. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Schmelling, M. Stahl, U. Uwer, M. Vesterinen, C. Voß, S. Wandernoth, A. Zhelezov [und 689 weitere]
Im Titel ist "0" hochgestellt, "s" ist tiefgestellt, dabei steht "s" unter "0"
Gesehen am 07.04.2021